TINGKAT ADOPSI KOMPONEN TEKNOLOGI USAHATANI PADI MELALUI SL-PTT DI LAHAN RAWA LEBAK TENGAHAN (Kasus di Kabupaten Hulu Sungai Selatan dan Hulu Sungai Utara Kalimantan Selatan) - Noorginayuwati ,; Khairil Anwar (Jurnal Pengkajian dan Pengembangan Teknologi Pertanian, 2015)
ABSTRACT Adoption of Rice Farming Technology through Field School-Integrated Crop Management (FFS-ICM) in Middle Back Swamp (Case study in Hulu Sungai Selatan and Hulu Sungai Utara Regency South Kalimantan). Back swamp has strategic role in the sustainability food self-sufficiency of rice. Since 2009 Farmers Field School of Integrated Crop Management (FFS-ICM) has been implemented to increase national productivity of rice involving 80,000 farmer groups on 2,050 million ha land area. The implementation of rice SL FFS-ICM on back swamp in South Kalimantan involved 325 farmer groups with 8,788 ha total area. The objective of the research was to determine adoption level of ICM technology; relationship between the adoption levels, productivity and implementation of rice FFS-ICM; and identify problems that occurred in the adoption process of technology components. The study was conducted in the two districts (HSS and HSU), four sub-district and six villages consisted of 6 farmer groups participants FFS-ICM and six farmer groups non participants of FFS-ICM. Sample farmers contained 120 respondents with 10 farmers per farmer groups. Data collection was conducted by survey method and interviews to the respondents by using questionnaire. Data analysis was performed using the scoring with 3 scales, Spearman rank correlation, mean and percentage. The results showed that adoption level of component technology ICM by participants of FFS-ICM and non participants FFS-ICM farmers were included the category of being with an average score of 23.98 (FFS-ICM) and 21.15 (non FFS-ICM). There was positive relationship between the adoption levels, productivity and implementation of SL-PTT. By adopting innovative technology components of ICM, the productivity increased 0.91 ton/ha and income raised by Rp2, 037,239. Problems on the adoption of ICM technology component was the lack of knowledge about seeds and miss matching planting systems and fertilizing used. It was because of lack of capital and limited of assessment of needs opportunities as well as evaluation of implementation of FFS-ICM. Keywords: Rice, component technology; adoption, FFS-ICM, middle back swamp ABSTRAKLahan lebak memiliki peran strategis dalam melestarikan swasembada beras. Pada tahun 2009 telah dilaksanakan Sekolah Lapangan Pengelolaan Tanaman Terpadu (SL-PTT) padi untuk meningkatkan produktivitas secara nasional yang melibatkan 80.000 kelompok tani dengan luas lahan 2.050 juta ha. Pelaksanaan SL-PTT padi di lahan rawa lebak Kalimantan Selatan melibatkan 325 kelompok tani dengan luas lahan 8.788 ha. Tujuan penelitian ialah mengetahui tingkat adopsi teknologi PTT, hubungan tingkat adopsi dengan produktivitas dan pelaksanaan SL-PTT padi serta mengidentifikasi permasalahan yang terjadi dalam adopsi komponen teknologi. Penelitian dilakukan di dua Kabupaten (Hulu Sungai Selatan dan Hulu Sungai Utara), empat kecamatan, enam desa yang terdiri atas enam kelompok tani peserta SL-PTT dan enam kelompok tani nonpeserta SL-PTT. Petani sampel ditentukan sebanyak 120 responden dengan 10 petani per kelompok tani. Pengumpulan data dilakukan dengan metode survei dan wawancara terhadap responden melalui pengisian kuesioner. Analisis data dilakukan menggunakan skor berjenjang 3, korelasi peringkat Spearman, rataan dan persentase. Hasil analisis menunjukkan bahwa tingkat adopsi komponen teknologi PTT petani peserta SL-PTT dan non peserta SL-PTT termasuk kategori sedang dengan rata-rata skor 23,98 (SL-PTT) dan 21,15 (nonSLPTT). Terdapat hubungan yang nyata antara tingkat adopsi komponen teknologi dengan produktivitas dan pelaksanaan SL-PTT. Dengan mengadopsi komponen teknologi PTT, produktivitas meningkat sebesar 0,91 ton/ha dan pendapatan sebesar Rp2.037.239. Adopsi komponen teknologi PTT menghadapi masalah yang disebabkan karena rendahnya pengetahuan tentang benih, tidak sesuainya rekomendasi sistem tanam dan pemupukan akibat kekurangan modal serta tidak didasari kajian kebutuhan dan peluang (KKP) serta belum dilaksanakan evaluasi SL-PTT. Kata kunci: Padi, komponen teknologi, adopsi, SL-PTT, lahan lebak tengahan